Intergenerational family narratives and their measurement among adults in the Czech Republic - Rynešová, Tereza (Civilia, 2023)
This text is a pilot study of a new method for measuring the level of knowledge of intergenerational family narratives among adults in Czech Republic, the Intergenerational Family Knowledge Questionnaire (in Czech language Dotazník mezigeneračních rodinných znalostí or DMRZ). The text first briefly introduces different types of family narratives with a focus on the characteristics of intergenerational family narratives. The main part of the text presents the creation of DMRZ. This method is based on the verification of knowledge of family history, which the individual knows from the stories of his ancestors. Three main thematic areas (knowledge of parents, grandparents, and early personal history) were defined, for which a total of 70 items were created. The pilot study was conducted on a sample of 107 Czech-speaking adults (63% women). Confirmatory factor analysis showed a better fit of the two-factor model consisting of 16 items from the thematic areas of knowledge about parents and grandparents. The newly developed method shows high internal consistency. The DMRZ is currently ready for research use and further validation.
Keywords: Family narratives; Intergenerational family narratives; Questionnaire; Identity; Psychological well-being